2018
DOI: 10.17509/ijal.v8i2.13311
|View full text |Cite
|
Sign up to set email alerts
|

CEFR-aligned school-based assessment in the Malaysian primary ESL classroom

Abstract: The Malaysian ESL (English as a Second Language) curriculum has undergone several reforms since the implementation of the Malaysian Education Blueprint 2013-2025. In 2016, the Kurikulum Standard Sekolah Rendah (KSSR) or the Standard Curriculum for Primary Schools (SBCPS), first introduced in 2011, was revised to align with the Common European Framework of References (CEFR) for languages. This more action-oriented approach resulted in fundamental changes to teaching, learning, and assessment including the integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 0 publications
5
44
0
Order By: Relevance
“…The introduction of CEFR into the Malaysian Education Blueprint 2013-2025 breathes a new life in the Malaysian ESL education system changing it from an exam-oriented to a more action-oriented approach (Abdul Hakim, Radzuwan & Wan Zhafirah, 2018). With it comes a focus on integrating innovative school-based, CEFR-aligned assessment with student-centred teaching and learning to develop autonomous language learners (Sidhu, Kaur & Lee, 2018). CEFR-aligned assessment tools such as language portfolio, peer or self-assessment and others are encouraged to be used in schools to consolidate the existing conventional teaching methods (Le, 2018;Read, 2019).…”
Section: R E S E a R C H O B J E C T I V E Smentioning
confidence: 99%
“…The introduction of CEFR into the Malaysian Education Blueprint 2013-2025 breathes a new life in the Malaysian ESL education system changing it from an exam-oriented to a more action-oriented approach (Abdul Hakim, Radzuwan & Wan Zhafirah, 2018). With it comes a focus on integrating innovative school-based, CEFR-aligned assessment with student-centred teaching and learning to develop autonomous language learners (Sidhu, Kaur & Lee, 2018). CEFR-aligned assessment tools such as language portfolio, peer or self-assessment and others are encouraged to be used in schools to consolidate the existing conventional teaching methods (Le, 2018;Read, 2019).…”
Section: R E S E a R C H O B J E C T I V E Smentioning
confidence: 99%
“…This indicated that they only have sound understanding of the assessment but unable to apply it in classroom practices. Sidhu, Kaur, & Chi (2018) further mentioned that although the teachers were aware that the current formative assessment includes assessment on oral proficiency, they admitted to not being adequately equipped with the knowledge and comprehension of the practices, assessment standards and types of assessment used. Fook & Sidhu (2006) also found that Malaysian ESL teachers possess limited knowledge in interpreting test scores, conducting item analysis and forming a test bank besides being unfamiliar with terms such as norm-referenced, criterion-referenced, formative and summative assessment.…”
Section: Language Assessment Literacy Among Malaysian Esl Teachersmentioning
confidence: 99%
“…Without good assessment practices, teachers may not be able to help advance students' learning (Fook & Sidhu, 2015). Nonetheless, previous studies in Malaysia revealed limited evidence of peer assessment in the primary ESL classroom (Sidhu, Kaur & Chi, 2016;Sardaneh, 2018) and teachers' inadequate knowledge and skills in implementing such type of assessment are cited as one of the contributing factors for the lack of peer assessment occurring in Malaysian classrooms (Sardaneh, 2018, Mohamad Uri & Abd. Aziz, 2018, Veloo et al, 2016.…”
Section: Introductionmentioning
confidence: 99%